Export Strategies of New Exporters: Why is Export Expansion Along the Extensive Margins so Sluggish? - Jože P. Damijan; Črt Kostevc; Sašo Polanec (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2011)
Recent theoretical models of international trade with heterogeneous firms feature instan- taneous adjustment of margins of exports to firm and market characteristics, and equality of distributions of margins of exports between new and incumbent exporters. By using the pop- ulation of Slovenian firms and their transaction-level trade data we document large differences between these firms that cannot be attributed to the differences in total factor productivity. This paper contributes to the field by demonstrating that access to financing, measured by eq- uity, debt-to-asset ratio and access to internal credit markets within firm groups, may account for an important part of observed differences in the extensive margins of exports between new and incumbent exporters.
Keywords: D24; F12; F14; 330; exports; multi-product firms; firm heterogeneity; financial constraints